Engineering Analysis with ANSYS Software - Stolarski, Tadeusz (Butterworth-Heinemann, 2006)
For all engineers and students coming to finite element analysis or to ANSYS software for the first time, this powerful hands-on guide develops a detailed and confident understanding of using ANSYS's powerful engineering analysis tools. The best way to learn complex systems is by means of hands-on experience. With an innovative and clear tutorial based approach, this powerful book provides readers with a comprehensive introduction to all of the fundamental areas of engineering analysis they are likely to require either as part of their studies or in getting up to speed fast with the use of ANSYS software in working life. Opening with an introduction to the principles of the finite element method, the book then presents an overview of ANSYS technologies before moving on to cover key applications areas in detail. Key topics covered: Introduction to the finite element method Getting started with ANSYS software stress analysis dynamics of machines fluid dynamics problems thermo mechanics contact and surface mechanics exercises, tutorials, worked examples With its detailed step-by-step explanations, extensive worked examples and sample problems, this book will develop the reader's understanding of FEA and their ability to use ANSYS's software tools to solve their own particular analysis problems, not just the ones set in the book. * Develops a detailed understanding of finite element analysis and the use of ANSYS software by example * Develops a detailed understanding of finite element analysis and the use of ANSYS software by example * Exclusively structured around the market leading ANSYS software, with detailed and clear step-by-step instruction, worked examples, and detailed, screen-by-screen illustrative problems to reinforce learning.